El marco TPACK y la creación de contenidos digitales en las prácticas de aula de docentes de educación básica (2024)
TPACK is a framework that guides the appropriate integration of technology in the classroom. The development of digital teaching skills is essential for teachers in the 21st century. The objective of this research was to analyze the technological knowledge of the TPACK framework used by in-services teachers of basic education in the classroom after participating in the NOOC focused on the creation of digital content. The research was developed under the qualitative paradigm through a case study of 4 teachers in service in basic and secondary education in the city of Bogota. The main results indicated that the course helped to strengthen the digital competence of teachers, as well as to identify elements associated with the pedagogical use of technology, such as support for class explanations, the use of multimedia resources to address different learning styles, and the motivation of students through the mediation of the teacher with the digital material developed and implemented in the classroom